The efficiency of estrus synchronization protocols and artificial insemination in the Abergelle goat on-station and on-farm conditions of Northern Ethiopia - Wondim, Bekahegn; Taye, Mengistie; Alemayehu, Kefyalew; Rouatbi, Mariem; Getachew, Tesfaye; Haile, Aynalem; Rekik, Mourad (Taylor and Francis Group, 2023)
This study was conducted to investigate the effect of different estrus synchronization protocols followed by artificial insemination on estrus response and the conception rate of Abergelle goats. Three estrus synchronization protocols: (i) the standard protocol associating progestogens, gonadotropins andprostaglandins (P4+ eCG + PGF2α), (ii) single injection of prostaglandin (PGFS), (iii) double injection ofprostaglandin (PGFD) were evaluated and compared to a control group that did not receive ahormonal treatment. Estrus behaviour was monitored in all does and those in estrus were inseminated. The estrous response was significantly higher in P4+ eCG + PGF2αdoes than in counter parts in PGFS and PGFD groups (p< 0.001). Results also revealed an earlier onset of estrus inthe PGFD-treated group, a longer duration of estrus for second- and third- parity -does and an earlier on set of estrus in animals having a 3.5 body condition score. Even if the conception rate (CR) washighest when using the PGFD protocol, the lowest kidding rate (KR) was obtained when using thissame treatment. The P4+ eCG + PGF protocol yielded the highest litter size. Farmers’ perception surveys revealed that a higher proportion of goat keepers used a controlled mating system and had culling practices and farmers selected PGFDas a preferred protocol.